Pigments based on Cr and Sb doped TiO2 prepared by microemulsion-mediated solvothermal synthesis for inkjet printing on ceramics - Jovani, Marc; Domingo, Maria; Machado, Thales R.; Longo, Elson [UNESP]; Beltran-Mir, Hector; Cordoncillo, Eloisa (Elsevier B.V., 2015)
A ceramic pigment with nominal composition Ti0.97Cr0.015Sb0.015O2 was prepared by microemulsion-mediated solvothermal method at 180 degrees C. Anatase or rutile single phase was obtained depending on the synthesis conditions. Scanning electron microscope analysis showed the formation of spheres with particle size around 600 nm. The anatase to rutile transformation temperature was determined by XRD and Raman spectroscopy. The evolution of the colour was studied, and it was related with the polymorphic transition. Yellow pigments were obtained at low temperature and huge orange colour was observed at high temperature. Powders prepared at 180 degrees C were tested with an industrial fit. Similar chromatic coordinates of an industrial orange ceramic pigment obtained at high temperatures were observed zeta-potential values of the particles were similar to-57 mV. The size, shape, colour and electrostatic stability of these particles make them potential candidates to be applied in glazes or inkjet printers as orange ceramic pigments. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Pigment; Titanium dioxide; Orange ceramic pigment; Inkjet; Ceramics; Solvothermal synthesis